1985
DOI: 10.1073/pnas.82.11.3601
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of methionine synthesis in Escherichia coli : Effect of metJ gene product and S -adenosylmethionine on the expression of the metF gene

Abstract: The regulation of the expression of the Escherichia coli metF gene, which codes for 5,10-methylenetetrahydrofolate reductase (EC 1.1.99.15), has been investigated by using a simplified DNA-directed in vitro system that measures the formation of the first dipeptide (fMet-Ser) of the gene product. The synthesis of fMet-Ser directed by a plasmid containing the metF gene is specifically inhibited by metJ protein (repressor protein). S-Adenosylmethionine enhances the inhibition by the metJ protein of metF gene expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
37
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 27 publications
(26 reference statements)
2
37
0
Order By: Relevance
“…The active form of MetJ represses the Met biosynthesis pathway (40). GSNO exposure results in decreased MetJ TFA (Fig.…”
Section: Gsno and No Inhibit Growth Through Distinct Mechanisms-mentioning
confidence: 95%
See 1 more Smart Citation
“…The active form of MetJ represses the Met biosynthesis pathway (40). GSNO exposure results in decreased MetJ TFA (Fig.…”
Section: Gsno and No Inhibit Growth Through Distinct Mechanisms-mentioning
confidence: 95%
“…4A). Met biosynthesis repressor MetJ requires binding of Met derivative S-adenosyl-L-methionine (AdoMet) for activity (40). CysB is a dual regulator that requires binding of Cys precursor acetylserine for activity (41).…”
Section: Gsno and No Inhibit Growth Through Distinct Mechanisms-mentioning
confidence: 99%
“…The promoters of these genes contain from 2 to 5 tandem repeats of the MetJ binding site, which are called metboxes and have the consensus sequence AGACGTCT (6). When MetJ is activated by S-adenosylmethionine (SAM) it binds tightly to the metboxes and shuts down transcription (7,8). The different genes repressed by MetJ not only have a variable number of metboxes but also variable sequences.…”
mentioning
confidence: 99%
“…Genetic studies suggest that an effector molecule controlling in vivo gpMetJ function is S-adenosyl methionine (Ado-met) (for reviews, see references 4, 8, 27). Recently, Shoeman et al (32) demonstrated that purified gpMetJ and Ado-met blocked metF expression at the level of RNA synthesis in an uncoupled DNA-directed protein synthesizing system. In the absence of Ado-met, high concentrations of gpMetJ also reduce in vitro metF expression.…”
mentioning
confidence: 99%
“…2A and B). Ado-met is the most probable candidate for this effector molecule (32,33). Therefore, the predicted decreases in the Ado-met and methionine pools, which result from the removal of the exogenous methionine supplement (Fig.…”
mentioning
confidence: 99%